Job Satisfaction, Leader Empowering Behaviors and Work Engagement Among Nurses in Tertiary Hospitals, Kunming, the People’s Republic of China - Duan Jinmei (Faculty of Nursing, Chiang Mai University, 2020)
Nurse Journal is an academic journal that disseminates nursing knowledge and midwifery, including new knowledge in health and is a medium for exchanging knowledge and opinions about the nursing profession and creating related relationships. Good relationship between colleagues and the image of the nursing profession, prepared by the Nurses Association of Thailand 4 times per year Nurse Journal is an academic journal that disseminates nursing knowledge and midwifery, including new knowledge in health and is a medium for exchanging knowledge and opinions about the nursing profession and creating related relationships. Good relationship between colleagues and the image of the nursing profession, prepared by the Nurses Association of Thailand 4 times per year